Measurement of inclusive charged-particle jet production in pp and p-Pb collisions at √sNN = 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; Nath, Abhishek; et al. (Journal of high energy physics, 2024)
Measurements of inclusive charged-particle jet production in pp and p-Pb collisions at center-of-mass energy per nucleon-nucleon collision √sNN = 5.02 TeV and the corresponding nuclear modification factor Rch jet pPb are presented, using data collected with the ALICE detector at the LHC. Jets are reconstructed in the central rapidity region |ηjet| < 0.5 from charged particles using the anti-kT algorithm with resolution parameters R = 0.2, 0.3, and 0.4. The pT-differential inclusive production cross section of charged-particle jets, as well as the corresponding cross section ratios, are reported for pp and p-Pb collisions in the transverse momentum range 10 < pch T,jet < 140 GeV/c and 10 < pch T,jet < 160 GeV/c, respectively, together with the nuclear modification factor Rch jet pPb in the range 10 < pch T,jet < 140 GeV/c. The analysis extends the pT range of the previously-reported charged-particle jet measurements by the ALICE Collaboration. The nuclear modification factor is found to be consistent with one and independent of the jet resolution parameter with the improved precision of this study, indicating that the possible influence of cold nuclear matter effects on the production cross section of charged-particle jets in p-Pb collisions at √sNN = 5.02 TeV is smaller than the current precision. The obtained results are in agreement with other minimum bias jet measurements available for RHIC and LHC energies, and are well reproduced by the NLO perturbative QCD Powheg calculations with parton shower provided by Pythia8 as well as by Jetscape simulations.
Gesehen am 17.06.2025